Ethnomathematical Practices and Agricultural Timing in Bugis Culture - Ja'faruddin, Ja'faruddin; Khaerati, Khaerati; Takdirming, Takdirming (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study delves into the realm of ethnomathematics within the Bugis culture, specifically examining how good and bad days for farming are determined. Utilizing a descriptive qualitative approach, the research involved direct observations at Fort Rotterdam, Makassar, alongside extensive literature reviews. The findings indicate that the division of good and bad days is based on distinct time cycles, represented by unique symbols that denote the quality of time. These traditions, passed down through generations, provide insights into the cultural values and beliefs of the Bugis community regarding the optimal timing for various activities. The symbols and guidelines not only embody cultural heritage but also illustrate the interplay between traditional time concepts and mathematical principles, such as patterns in calendar calculations. In Bugis culture, time is more than just the passage of hours—it is a living guide that intertwines spirituality with daily life. Terms like Empty, Dead, Alive, Even, and Full are imbued with profound meanings that influence their actions, ensuring harmony with natural and spiritual rhythms. The traditional time-scoring system maintains balance, but skipping intervals like midday or afternoon can significantly alter the day's designation. Analyzing daily scores and excluded intervals highlights how time segments impact activities and symbolism, with Wednesday and Saturday deemed particularly suitable for farming.